2018
DOI: 10.1096/fj.201800500r
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose 6‐phosphate phosphatases ofPseudomonas aeruginosa

Abstract: The opportunistic bacterium Pseudomonas aeruginosa has been recognized as an important pathogen of clinical relevance and is a leading cause of hospital-acquired infections. The presence of a glycolytic enzyme in Pseudomonas, which is known to be inhibited by trehalose 6-phosphate (T6P) in other organisms, suggests that these bacteria may be vulnerable to the detrimental effects of intracellular T6P accumulation. In the present study, we explored the structural and functional properties of trehalose 6-phosphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 88 publications
(81 reference statements)
0
10
0
Order By: Relevance
“…EDTA has no clinical utility as an antibacterial, but inhibitors with greater specificity have been reported. For example, trehalose 6 phosphate has been reported to be an inhibitor of the P. aeruginosa OtsB [ 75 ]. In M. smegmatis and M. tuberculosis the antibiotics diumycin and moenomycin can inhibit OtsB activity, but the doses required for 50% inhibition are high (50 and 100 µg/ml) and these drugs were less active toward the M. tuberculosis enzyme [ 76 ].…”
Section: Introductionmentioning
confidence: 99%
“…EDTA has no clinical utility as an antibacterial, but inhibitors with greater specificity have been reported. For example, trehalose 6 phosphate has been reported to be an inhibitor of the P. aeruginosa OtsB [ 75 ]. In M. smegmatis and M. tuberculosis the antibiotics diumycin and moenomycin can inhibit OtsB activity, but the doses required for 50% inhibition are high (50 and 100 µg/ml) and these drugs were less active toward the M. tuberculosis enzyme [ 76 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given the exquisite substrate specificity of TPPs 3235 , there is a strict requirement for the original and rather expensive substrate trehalose-6-phosphate in enzyme assays testing the activity and inhibition of these proteins. Therefore, we employed an economical two-tiered screening approach that consisted of a first-stage screening of compound libraries with a ligand binding assay based on thermal protein denaturation and a second-stage validation of hits in enzyme activity assays 31,36 .…”
Section: Resultsmentioning
confidence: 99%
“…The reason for this susceptibility is not entirely clear, but we speculate that the conjugation of one or both cysteine residues specific to P. aeruginosa (Cys85, Cys231) might lead to conformational alterations that restrict access to the substrate binding site. In particular, it seems likely that modification of the side chain of Cys85 causes a rearrangement of the residues lining the rather narrow access to the active site 35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the effort in these studies has been directed toward investigating the impact of diffusion in fractal media on the reaction kinetics (22), with little focus on characterizing the effect of crowding on the mean effective enzyme kinetics. However, because it has now been shown that in vitro, some enzymes might not be limited by their translational diffusion but by their apparent association rate constants (24)(25)(26)(27)(28), the reevaluation of crowding in these reactions is important. In this work, therefore, we introduced computational methods for studying spatial effects of any kind, applying our work to the effects of crowding on reaction-limited enzymes with the goal of bridging the discrepancy between the in vitro measurement of kinetic parameters and the actual in vivo conditions.…”
Section: Introductionmentioning
confidence: 99%